Hierarchy in the Halogen Activation During Surface‐Promoted Ullmann Coupling. Issue 18 (20th August 2019) - Merino‐Díez, Néstor; Pérez Paz, Alejandro; Li, Jingcheng; Vilas‐Varela, Manuel; Lawrence, James; Mohammed, Mohammed S. G.; Berdonces‐Layunta, Alejandro; Barragán, Ana; Pascual, Jose Ignacio; Lobo‐Checa, Jorge; Peña, Diego; de Oteyza, Dimas G.
Abstract: Within the collection of surface‐supported reactions currently accessible for the production of extended molecular nanostructures under ultra‐high vacuum, Ullmann coupling has been the most successful in the controlled formation of covalent single C−C bonds. Particularly advanced control of this synthetic tool has been obtained by means of hierarchical reactivity, commonly achieved by the use of different halogen atoms that consequently display distinct activation temperatures. Here we report on the site‐selective reactivity of certain carbon‐halogen bonds. We use precursor molecules halogenated with bromine atoms at two non‐equivalent carbon atoms and found that the Ullmann coupling occurs on Au(111) with a remarkable predilection for one of the positions. Experimental evidence is provided by means of scanning tunneling microscopy and core level photoemission spectroscopy, and a rationalized understanding of the observed preference is obtained from density functional theory calculations. Abstract : The presence of carbon‐bromine bonds with similar gas‐phase binding energies allows the Ullmann coupling to occur via two different orientations. However, upon adsorption on Au(111), one particular type of carbon‐bromine bond is preferentially cleaved, thus selecting a coupling route that leads to the formation of chiral graphene nanoribbons. Nevertheless, the occasional coupling along the second orientation also leads to the lateral fusion of the nanoribbons even at mild temperatures.